Positive Politeness Strategies in the 2025 Grammy Awards Acceptance Speech - Aldiansyah Munawar Al Fachri; Abd Hannan EF; Dedi Sulaeman (Universitas Pahlawan Tuanku Tambusai, 2026)
The Grammy Awards is an annual event of American music industry. This ceremony is closely linked to the award acceptance speeches given by each category's nominee winners. In order to preserve their image, celebrities typically pay attention to word choice. The research objective is to analyze how positive politeness strategies are linguistically realized and function pragmatically in acceptance speeches. Nine selected speeches by Grammy Award winners were analyzed using the positive politeness strategies theory proposed by Brown and Levinson (1987). By using a qualitative descriptive method, the data were described based on their sub-categories. Therefore, the result of the study showed that eleven of the fifteen positive politeness sub-categories are generally found in the award acceptance speech. By employing positive politeness strategies, celebrities are able to construct a positive public image, which enhances their likability and public perception.